Comment On: Vonoprazan on the Eradication of Helicobacter pylori Infection - Tolga Düzenli; Hüseyin Köseoğlu; Muhammed Kaya; Mesut Sezikli (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Düzenli T, Köseoğlu H, Kaya M, Sezikli M. Comment on: Vonoprazan on the eradication of Helicobacter pylori infection. Turk J Gastroenterol. 2023;34(4):435-436